Thermodynamics of melting relations in the system Fe‐FeO at high pressure: Implications for oxygen in the Earth's core. Issue 5 (20th May 2014) - Komabayashi, Tetsuya
Abstract: The thermodynamics of melting relations in the system Fe‐FeO was investigated to the outer core–inner core boundary condition from a self‐consistent thermodynamic database which was evaluated from the latest static high‐pressure ( P ) and high‐temperature ( T ) experiments. The evaluated database together with an existing nonideal mixing model for liquids reproduces experimental data on the eutectic composition and temperature to P = 50 GPa. On the other hand at the outer core pressures (136 to 330 GPa), employing an ideal solution model gives calculated eutectic temperatures of T = 2990–4330 K, which are also consistent with experimental data. Hence, the ideal solution model is applied to calculate the liquid property under outer core conditions and yields the eutectic compositions of Fe–7.2–9.1 wt % O. From the Gibbs free energy for the Fe‐FeO liquids, I calculated the density, sound velocity, and isentropic temperature gradient of a hypothetical oxygen‐bearing outer core. Under the outer core conditions, the addition of oxygen reduces the compressional wave velocity of iron liquid, moving it away from seismologically constrained values. An overall O‐rich bulk outer core model is thus excluded. Seismological observations however suggest the presence of a low‐velocity layer with a thickness of 60–70 km at the top of the outer core. The origin of such a low‐velocity layer can be explained by an enrichment of oxygen which might be a consequence of chemical interactions between the core and mantle. Key Points: Melting relations in the system Fe‐FeO was modeled to 330 GPa Addition of oxygen reduces velocity of iron liquid under outer core conditions Bulk outer core is oxygen‐poor while topmost of the core is oxygen‐rich